Manajemen Pemanfaatan Smart City dan Keaslian Al-Qur’an dalam Pendidikan Agama Islam melalui Teknologi Digital: Smart City Utilization Management and the Authenticity of the Qur'an in Islamic Religious Education through Digital Technology - Dede Ridho Firdaus; Novia Permata Atmadja (ITScience (Information Technology and Science), 2026)
This study aims to analyze the management strategy for utilizing smart cities in religious education to optimize access and maintain the authenticity of the Qur'an through digital technology. The development of smart cities and digitalization in Indonesia presents significant opportunities for Islamic religious education, particularly for expanding the reach of learning and ensuring the authenticity of teachings through digital systems. The research method used is a Systematic Literature Review (SLR) of literature published between 2020 and 2025, focusing on integrating technologies such as Artificial Intelligence, the Internet of Things, and cloud computing to manage Qur'an education. The analysis results show that implementing digital management strategies can improve the efficiency of access, learning, and the verification of the authenticity of Qur'an manuscripts. However, challenges remain in the digital infrastructure gap, educators' readiness, and the need for policies and regulations to standardize digital religious content. The digital technologies used in this study include officially licensed products such as mobile Qur'an applications, cloud computing systems, and artificial intelligence, which ensure the security, authenticity, and quality of digital Qur'an learning. The practical implication of this research is the need for collaboration among government institutions, schools, and the community to develop an innovative, technology-adaptive religious education management system. This research contributes to the development of a smart-city-based religious education management model that can shape a generation of religious, tech-savvy, and virtuous Quranists in the smart-city era.